Keeping a close watch on innovation studies: Opening the black box of journal editorships - Santos, A. T.; Mendonça, S. (Quantitative Science Studies, 2024)
Editors are journals’ entrepreneurs, managers, and stewards. They have the duty of holding high standards of scholarly quality in terms of end product (articles) and due process (adequate peer-review procedures). Given the importance of journals in the contemporary science “ecosystem,” editors emerge as decisive power brokers. Elite board members are scrutinizers but, paradoxically, they are themselves seldom subject to systematic study. This paper presents a comprehensive portrait of the editorship phenomenon in Innovation Studies by probing the structural features of the boards of 20 leading innovation-oriented journals as of 2019 and conducting an editor survey. We account for 2,440 individual editors in 3,005 different roles based in 53 countries. We uncover the overwhelming dominance of U.S.-affiliated editors and the contrasting rare presence of scholars from the Global South. The gender balance tilts toward men, with a weight above 60%. Enhanced journal achievement is associated with editors on multiple boards, diverse national representation, and increased women on boards. Almost 20% of scholars serve on multiple boards, and no single journal is free from this interlocking editorship phenomenon. The journal Research Policy is the most central in the cross-board network, followed by Industrial and Corporate Change. Finally, the implications of editormetrics for journal governance are discussed.